Uterine dystopias. - Lozada Stanbury, B. (2015)
We know that any segment of the genital tract, can be a vice seat position or dystopia, this is a waste of anatomical relationship to its location and its attachment and support structures. Some of these dystopias have greater clinical significance, for example if it happens in the fallopian tubes; however with regard to the uterus, they have sufficient seniority in Gynecology for study.